Modern Life as a Factor of Childhood Obesity: A Brief Review - Warly Neves de Araujo; Randra Karoline Rodrigues Inacio; Amanda Aguiar Barros; Daniela Santos do Nascimento; Eva Coelho da Silva; Agrinazio Nascimento Neto; Jefferson Rodrigues de Souza; Taiany Neves de Araujo; Daniela Ponsiano Oliveira; Sávia Denise Silva Carlotto Herrera; Ligiane Rodrigues de Souza; Daniela Pereira da Rocha; et al. (Archives of Current Research International, 2020)
Childhood obesity has grown worryingly on a global scale one of the biggest influencers are technological advances exposed early to children. Therefore, this study aimed to seek in the literature the relationship between modernity and the high incidence of children above their ideal weight. The research is a systematic literature review on the factors that are linked to the high prevalence of children above their ideal weight today. After the analysis of the studies, it is notorious the impact generated by technology on the health and development of children when they are used early. Concluding the present study that the negative factors that have been contributing to the triggering of childhood obesity are: passive habits, that is, little physical activity, the large number of hours spent in front of TV, video game, DVD between Other electronic devices this combined with poor consumption feeding of high fat and sugar products and lack of physical exercise are factors that reflect a negative response in children’s lives favoring body fat accumulation.